Rheological properties of dairy desserts: Effect of rice bran protein and fat content. Issue 11 (28th September 2022) - Mohammadi, Atefeh; Shahidi, Seyed‐Ahmad; Rafe, Ali; Naghizadeh Raeisi, Shahram; Ghorbani‐HasanSaraei, Azade
Abstract : Abstract: Rice bran protein (RBP) is an alternative plant protein that can be used in a wide range of foods due to its unique functional, nutritional, and hypoallergenic properties. The interactions of RBP with other biopolymers have revealed its feasibility for application in dairy products such as whipped cream and dairy desserts. Therefore, the effects of RBP and fat content on the rheological properties of dairy desserts were investigated. The pH value was not influenced by protein, but the nonfat milk solid content was changed by fat and protein content. All the desserts showed thixotropic properties which were mainly related to the molecular disentanglement at high shear rates. By increasing fat like RBP, the apparent viscosity ( ηa ) was increased. Rheological parameters such as n value, thixotropic index, storage (G′), and loss moduli (G′′) were increased by RBP. Moreover, the dairy desserts containing RBP and whole milk presented generally higher G ′, G ′′, complex modulus, and complex viscosity values, and lower tan δ values. The RBP enriched samples also had a higher hardness and gumminess. Syneresis was decreased by RBP, which was related to the formation of ordered mesh‐like structures which enabled the entrapment of more water. There was a positive correlation between the rheological, textural, and physical properties of the dessert with added RBP, and therefore dairy dessert attributes can be improved along with fat reduction. However, a sensory evaluation is needed to unravel the acceptability rate of RBP in fat reduction from the view point of consumers. Practical Application: Rice bran protein (RBP) has nutritional and hypoallergenic properties which enable it to apply to many products such as dairy desserts. One of the main concerns in dairy technology is the growing interest in low‐fat products due to health problems. RBP showed unique properties which makes the creamy behavior. The rheological results have elucidated the creaminess associated with RBP and can assist in the proper simulation of mouthfeel.